A Review Study on Green Tea and Its Health Benefits (International Journal of Innovative Research in Computer Science & Technology, 2021)
The Camellia sinensis plant conveys an  extent of white, green, or dull teas. Tea is among the most  notable beverages on earth, behind water similar to joy or  clinical benefits. Green tea is more imperative than dull tea  to the extent that reasonability. Polyphenols are the  imperative pieces of importance since they are major for  green tea's malignant growth avoidance specialist or other  clinical benefits. Green tea's most abundant polyphenols are flavonoids. The four fundamental flavonoids contained in  green tea are epicatechin (EC), epicatechin gallate (ECG),  epigallocatechin, and epigallocatechin gallate (EGG).  Epigallocatechin gallate is the super powerful part. The  procedures used to make dull tea are seen to lessen  monomeric catechin levels by and large more than those used  to make various teas. There is a lot of verification that green  tea enjoys health advantages for a variety of difficulties,  including threatening development, liver ailment, coronary  ailment, and so on Green tea might even guide in the  treatment of diabetes, combustible inside disease, work out,  skin conditions, going bare, shedding pounds, or iron over trouble, among something else. This article will go through  the critical clinical benefits of green tea, with an accentuation  on catechins.
Keywords: Black Tea; Green Tea; Health; Polyphenols Tea